ANALISIS PERDAGANGAN JAGUNG INDONESIA - Muhammad Imam Ma'ruf (Agro Ekonomi, 2010)
Corn has a strategic role and economic value in Indonesia, and has to be developed due to its position as the main source of carbohydrate and protein, raw material for food, feed, and biofuel industry. Aimed this research to determine the position of Indonesian com competitiveness in the international market in know the comparative advantage of Indonesian corn;factors that influence Indonesian com demand, and the integration between Indonesian corn market and the world com market. This research applys descriptive method The data used are time series data sourced from FAO, National Statistic Agency (BPS), and World Bank. Competitiveness is measured by the parameters of Revealed Comparative Advantage, Trade Specialist Ratio, Acceleration Ratio, and Market Penetration Index. The RCA, TSR, and AR analysis used data year 1988-2008, the MPI analysis used data year 1995-2008. Indonesian import corn demand is analyzed by OLS (ordinary least squares) multiple regression in the form of natural logarithm using data year 1980-2008, while market integration is analyzed by the unit root test, co-integration test, and Granger causality test using data year 1961-2008. The results shows that 1) the Indonesian corn competitiveness is low caused by the low production of Indonesian com; 2) Indonesian import corn demand is positively affected by the price of imported com and GDP of Indonesia, and negatively affected by the price of imported soybean and imported rice. Imported soybeans are complements of cornfor feed, while imported rice is the substitute of com for feed,' 3) There is no integration between the Chinese market and the Indonesian market because China is a country which re-export corn, there is integration between the United States market and the Indonesian market, as well as between Argentina's market and Indonesian market, but there is no causal relationship. The United States and Argentina market is not a dominant (leading) market in pricing of Indonesian Corn.market.